2007
DOI: 10.1016/j.ejpain.2006.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Acute muscle inflammation enhances the monosynaptic reflexes and c‐fos expression in the feline spinal cord

Abstract: The aim of this research was to study the changes of the motor reflex activity (monosynaptic reflex (MSR) of the flexor and extensor muscles) and Fos immunoreactivity in lumbo-sacral spinal cord after acute induced myositis of m. gastrocnemius-soleus (GS). The experiments were carried out on ischaemic decerebrated, spinalized in C1 cats. After infiltration of the GS muscle with carrageenan (2%) MSRs of flexors and extensors showed a significant increase in amplitude +127+/-24.5% and +155+/-28.5%, respectively,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 35 publications
(73 reference statements)
1
13
1
2
Order By: Relevance
“…Such modifications correlate with the data on the role of recurrent proprioceptive influences in the maintenance of the muscle function upon excessive loadings [7]. At the same time, inflammation of the skeletal muscles [6] is accompanied by a considerable enhancement of the influences from group Ia afferents and of Fos immunoreactivity, i.e., manifestations that can be correlated with a specific complex of symptoms typical of myositis.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…Such modifications correlate with the data on the role of recurrent proprioceptive influences in the maintenance of the muscle function upon excessive loadings [7]. At the same time, inflammation of the skeletal muscles [6] is accompanied by a considerable enhancement of the influences from group Ia afferents and of Fos immunoreactivity, i.e., manifestations that can be correlated with a specific complex of symptoms typical of myositis.…”
Section: Introductionmentioning
confidence: 56%
“…Estimation of the expression of c-Fos, a "fast-response" protein, is at present effectively used for identification of the neurons, which are components of the pathways related to realization of definite specific functions [1]. Modern studies of neuronal activity using this immunohistochemical technique of visualization of c-Fos in spinal neurons upon selective activation of intrafusal muscle fibers were stimulated by the existence of the data obtained in immunohistochemical [2,3] and electrophysiological studies of the role of proprioceptive impulsation from the skeletal muscles [4][5][6]. As was noted, the development of fatigue in such muscles is accompanied by some decrease in the intensity of impulsation of Ia fibers and parallel suppression of the activity of homonymous motoneurons.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained data indicate that substantial changes in the segmental reflex mechanisms can be triggered during chronic muscle inflammation. Recently, non-reciprocal excitation of both flexor and extensor motoneurons after acute carrageenan-induced muscle inflammation has been shown [8]. A reduction of the bilateral withdrawal thresholds and increased hyperalgesia after FCA-induced muscle inflammation were also demonstrated [28].…”
Section: Discussionmentioning
confidence: 97%
“…Mechanical or chemical activation of primary Aδ and C muscle afferents induces c-fos expression in spinal neurons [4][5][6][7]. It was recently shown that the development of carrageenaninduced acute experimental myositis was followed by a significant increase in the efficacy of the Ia input to spinal motoneurons, which was accompanied by a strong enhancement of c-fos expression in the dorsal and ventral horns of the spinal gray [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation